Minding Dogs : Humans, Canine Companions, and a New Philosophy of Cognitive Science - Merritt, Michele, 1980- (Book collections on Project MUSE., 2021)
"The past decade has seen a surge of interest in canine cognition. This newfound interest, however, has not caught the attention of many philosophers. Studies pertaining to dog minds have been pouring out of canine cognition labs all over the world, but they remain relatively ensconced within the scientific, sociological, and anthropological communities. Besides dogs, researchers have also been probing the minds of octopi, fish, and crows, and indeed, several philosophers have weighed in on these findings. Nevertheless, very little philosophical thought on dog cognition exists. Philosophers certainly have not shied away from theorizing about the nature of non-human animal cognition generally. Theories range from Cartesian disavowal of all non-human intelligence to arguments that even fish have complex minds and therefore, humans should not eat them. Serious philosophical considerations about dogs and their relationship to humans, however, remain incredibly rare. Several philosophers have contributed to this discussion, primarily in the hopes of determining how the canine mind works and what it's like to be a dog, but again, this is uncommon. Even less common, if not entirely nonexistent, is a critical examination of this very question - what are dogs thinking? - and what asking and attempting to answer this question reveals, not so much about dogs, but about us. This book marks the beginning of attempting to fill two significant gaps in the philosophy of animal cognition. First, it adds to the growing discussion on canine cognition, which has been overlooked until recently, and is in need of more consideration. Second, it takes seriously our relationship and co-evolution with our canine friends as crucial to understanding both their minds as well as our own"--